David W.J. Gill, Winifred Lamb: Aegean Prehistorian and Museum Curator. - Tzortzopoulou-Gregory, Lita (Journal of Greek Archaeology, 2022)
David W.J. Gill, Winifred Lamb: Aegean Prehistorian and Museum Curator. pp. vi + 276, Oxford: Archaeopress, 2018. ISBN 978-1-78491-879-8, paperback £30; 978-1-8491-880-4, E-book £16.